High–Frame Rate Vector Flow Imaging of the Carotid Bifurcation in Healthy Adults: Comparison With Color Doppler Imaging. (25th March 2018) - Goddi, Alfredo; Bortolotto, Chandra; Raciti, Maria Vittoria; Fiorina, Ilaria; Aiani, Luca; Magistretti, Giovanni; Sacchi, Andrea; Tinelli, Carmine; Calliada, Fabrizio
Abstract : Objectives: To evaluate the carotid bifurcation in healthy adults using a commercial system equipped with high–frame rate vector flow imaging (VFI) based on the plane wave and to compare VFI with color Doppler imaging. Methods: Carotid bifurcation diameters and flow characteristics of 60 vessels in 60 healthy volunteers were evaluated quantitatively and qualitatively to assess complex flow patterns and their extension and duration. Results: Complex flow in the internal carotid artery (ICA) was associated with a statistically significant difference in the ΔICA sinus‐to‐common carotid artery (CCA) diameter ratio (the relative change in diameter between the CCA and ICA sinus.) Vector flow imaging and color Doppler imaging were in accordance when detecting complex flow in 96.7% of cases; in 3.3% of cases, only VFI identified small recirculation areas of short duration. Vector flow imaging highlighted a larger extension of the complex flow (mean ± SD, 47.7 ± 28.5 mm 2 ; median, 45.5 mm 2 ) compared with color Doppler imaging (mean, 29.2 ± 19.9 mm 2 ; median, 29.5 mm 2 ) and better depicted different complex flow patterns; a strong correlation ( r  = 0.84) was found between the ΔICA sinus‐to‐CCA diameter ratio and the complex flow extension. Vector flow imaging showed a longer duration of the flow disturbances (mean, 380 ± 218 milliseconds; median, 352.5 milliseconds) compared with color Doppler imaging (mean, 325 ± 206 milliseconds; median, 333 milliseconds), and there was a strong correlation ( r  = 0.92). Conclusions: Vector flow imaging is as effective as color Doppler imaging in the detection of flow disturbances, but it is more powerful in the assessment of complex flow patterns.